Membangun Komunitas Muslim Digital: Edukasi dan Aplikasi Digitalpreneur dan Pembelajaran Inovatif bagi Guru Madrasah desa Gunung Leutik - Allya Roosallyn Assyofa; Nadri Taja; Ulvah Nur’aeni (Jurnal Dharma Bhakti Ekuitas, 2025)
Developing the competency of Madrasa teachers is crucial in facing the 21st-century education’s challenges, where the growth of Madrasas needs to be balanced with the quality of their educational services. Teacher performance in the field of teaching still does not meet standards. Inaccurate use of learning models is an obstacle to creating effective learning activities and achieving expected learning outcomes. On the other hand, most madrasa teachers still experience limited fixed income that is insufficient to meet daily living needs. The purpose of this community service project is to raise the proficiency of madrasa teachers in developing innovative learning methods while building digital entrepreneurial capacity (digital preneur). The activity was carried out in Desa Gunung Leutik, Ciparay, Bandung, with partners from the Diniyah Takmiliyah Communication Forum (FKDT), consisting of 30 teachers from 16 madrasas. The implementation method included training, mentoring, and direct practice/workshops on the use of appropriate applications and technology. The results of the activity demonstrated an increase in teacher competencies in applying cooperative learning, problem-based learning, and contextual teaching and learning models. In addition, participants will be able to utilize the Hadith Soft application as a source of teaching materials, develop Muslim entrepreneurial character, understand the basics of business management, and optimize digital media for product marketing. This program has implications for strengthening Madrasa teachers’ dual function as both educators and change agents in digital-based economic empowerment within Madrasa and community. Keywords: community service, digital preneur, innovative learning, madrasa, teacher competencies Abstrak   Pengembangan kompetensi guru madrasah menjadi kebutuhan penting dalam menghadapi tantangan pendidikan abad 21, dimana pertumbuhan madrasah perlu diimbangi dengan kualitas layanan pendidikannya. Kinerja guru dalam bidang pengajaran masih belum memenuhi standar. Ketidaktepatan dalam menggunakan model pembelajaran menjadi kendala dalam menciptakan kegiatan pembelajaran yang efektif dan capaian pembelajaran yang diharapkan. Di sisi lain, sebagian besar guru madrasah masih mengalami keterbatasan penghasilan tetap yang belum mencukupi memenuhi kebutuhan hidup sehari-hari. Tujuan dari proyek pengabdian masyarakat ini adalah untuk meningkatkan kemahiran guru madrasah dalam mengembangkan metode pembelajaran yang inovatif sambil membangun kapasitas kewirausahaan digital (digital preneur). Kegiatan dilaksanakan di Desa Gunung Leutik, Kecamatan Ciparay, Kabupaten Bandung dengan mitra Forum Komunikasi Diniyah Takmiliyah (FKDT) yang terdiri atas 30 guru dari 16 madrasah. Metode pelaksanaan meliputi pelatihan, pendampingan, serta praktik langsung/workshop penggunaan aplikasi dan teknologi tepat guna. Hasil kegiatan menunjukkan adanya peningkatan keterampilan guru dalam mengaplikasikan model pembelajaran cooperative learning, problem-based learning, dan contextual teaching and learning. Selain itu, peserta mampu memanfaatkan aplikasi Hadits Soft sebagai sumber materi ajar, mengembangkan karakter wirausaha muslim, memahami dasar-dasar manajemen usaha, serta mengoptimalkan media digital dalam pemasaran produk. Program ini berimplikasi pada penguatan dwifungsi guru Madrasah sebagai pendidik sekaligus agen perubahan dalam pemberdayaan ekonomi berbasis digital di lingkungan Madrasah dan masyarakat. Kata kunci: pengabdian masyarakat, digitalpreneur, pembelajaran inovatif, madrasah, kompetensi guru